(untitled) (Journal of Forestry, 2024)
The current study aims to evaluate the effect of the wild pear (Pyruspyraster (L.) Burgsd.) fruit size on morphological fruit and seed traits. Wild pear fruit was collected from 10 trees in the Žumberačko gorje area in the fall of year 2022. Fruits were randomly collected from the ground and divided into three groups according to their weight (small (<10g), medium (10 – 15g) and large (>15g)). Fruit size had significant effect on following morphological traits: fruit weight, fruit length, fruit width, number of filled seeds, weight of fresh seed per fruit, weight of 1 fresh seed and weight of air-died seed; while for fruit shape index, number of empty seeds, weight of 1 air dried seed and share of seed dry matter no significant difference was recorded. For all aforementioned traits were difference was significant, large fruit had significantly highest values, while in most cases (with exception of weight of 1 fresh seed) medium fruit had significantly higher values than small one. When correlation coefficients between different fruit size groups are compared, it is evident that higher fruit size traits had significant effect on the number of filled seeds only in medium and large wild pear fruit. In addition, it is visible that of fruit size parameters, fruit weight and width, and not fruit length, had majority of impact on number of filled seeds. Principal component analysis revealed 3 significant principal components having eigenvalues higher than 1, that explained 75.88% of total variability. It showed that large fruit distinguish themselves between small and partly between medium by F1 axis. F1 was mostly influenced by fruit weight, fruit length, fruit width, number of filled seeds, weight of fresh seed per fruit and weight of air dried seed per fruit. According to results obtained from this study it can be concluded that for nursery production of wild pear seedlings bigger fruit should be used due to their higher number of filled seeds.